Duality between coordinates and Dirac field - Abdalla, MCB; Gadelha, A. L.; Vancea, IV (Elsevier B.V., 2000)
The duality between the Cartesian coordinates on the Minkowski space-time and the Dirac field is investigated. Two distinct possibilities to define this duality are shown to exist. In both cases, the equations satisfied by prepotentials are of second order. (C) 2000 Elsevier B.V. B.V. All rights reserved.